Variabilité Morphologique Et Agronomique Des Morphotypes De Voandzou (Vigna Subterranea (L.) Cultivés Dans La Zone Sahélienne Du Niger - Amadou Harouna Issa; Agali Alhassane; Sani Daouda Ousmane; Souleymane Boureima Kodo (European Scientific Journal, ESJ, 2018)
In Niger, Bambara groundnut is mainly grown by women in pure culture on small areas and without improved technics. However, improving the production of this crop can help to ensure food security. Knowledge of Bambara groundnut's diversity will allow its use in breeding programs. This study concerns the agro-morphological characterization in the Sahelian agroclimatic zone of fourteen (14) morphotypes of Bambara groundnut identified in the Nigerien accessions collection. The data used are collected through an agronomic test using a complete random block design, with four repetitions. Twelve (12) characters including 01 phenological, 08 morphological and 03 related to the yield components at harvest were evaluated. Descriptive statistical analysis showed that the coefficients of variation ranged from 10.3% (early flowering) to 72% (seeds weight per plant). Significantly high values (CV> 20%) were observed for 07 characters out of 12 analyzed. Agromorphological characterization revealed significant differences between the 09 parameters of the morphotypes. It was found that the Ne-10 and Ne-14 morphotypes are more efficient in grain yield, with 10.8 and 9.6 g / plant, respectively. Late-flowering morphotype (Ne-01) had the lowest yield. Strong correlations were observed in the morphological parameters, with r = 0.82 between the petiole length and the width of the terminal leaflet. A correlation of the same order was obtained between the wingspan of the plant and the width of the terminal leaflet, with r = 0.76. For yield parameters, strong correlations were observed between seed weight per plant and pod weight per plant (r = 0.96), and between same seed weight and number of pods per plant (r = 0.87). The dendrogram classified the morphotypes into 4 groups, with the Ne-14 and Ne-01 morphotypes each forming two isolated groups, the Ne-04 and Ne-08 morphotypes forming the third group and the 10 others together constituting the fourth group.